Peran E-Wallet dalam Meningkatkan Inklusi Keuangan Digital pada Gen Z Siswa SMA Triguna 1956 Jakarta - Sareza Lizatuzzahra; Najwa Syaifudin; Davina Elgia Putri; Yeni Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Gen Z is the age group most familiar with digital technology, including in financial transactions and management. However, low digital financial literacy means many students lack a clear understanding of the benefits, risks, and wise use of e-wallets and fintech. This Community Service (PKM) activity aims to improve the understanding of digital financial literacy among TRIGUNA 1956 High School students, particularly the use of e-wallets as a means of financial inclusion. The program was implemented through outreach, interactive discussions, and educational games covering e-wallet functions, transaction methods, digital security, the risks of misuse, and strategies for avoiding digital fraud. The results of the activity showed that students demonstrated high enthusiasm and were able to understand the basic concepts of e-wallets, the importance of managing digital finances, and recognize the signs of online fraud. This activity demonstrates that technology-based financial literacy education has a significant impact on increasing students' digital financial awareness and skills. With this provision, students are better prepared to face the development of financial technology in their daily lives.